Diversity, public space and places of encounter: - Donya Ahmadi (A+BE: Architecture and the Built Environment, 2018)
Increasingly, public spaces are being regarded as important resources for fostering multi-cultural coexistence and for creating opportunities for cross-cultural understanding and dialogue, in that they can provide a platform wherein interactions across diverse backgrounds occur. This article explores the perceptions of public place in a highly diverse, post-war, modernist suburb of Toronto, and the extent to which public spaces play a role in fostering interactions between different groups and catering for diversity in the area. The analysis indicates that there is little evidence for encounters between diverse groups in public spaces, due to the lack of spatial infrastructure anticipated in the modernist design of the neighbourhood. In addition, social factors such as surveillance and policing, lack of appropriate symbols that cater to different user groups, and presence of gangs and violence have resulted in residents’ self-exclusion from public spaces and undermined the frequency and quality of their social encounters.